Elementary principles of chemical processes - Felder, Richard M. (Wiley, 2005)
Material that's presented in a very clear and accessible way ... frequent use of examples ... case studies based on commercial processes ... a CD-ROM with instructional tutorials, a powerful equation solver, and a visual encyclopedia of chemical process equipment ... These are just a few of the features of this text that help provide a realistic, informative introduction to chemical processes.